Socioeconomic and technical considerations to mitigate land and water degradation in the Peruvian Andes - Torero, M.; Zegarra, E.; Pender, J.L.; Maruyama, Eduardo; Keefe, M.; Stoorvogel, J.J. (CGIAR Challenge Program on Water and Food, 2010)
This project aims to increase agricultural productivity, incomes, and sustainable management of land and water by small farmers in the rural Sierra region of Peru. Although results demonstrate the effectiveness of increased productivity and commercialization of high value agricultural commodities, this type of activity may be limited to certain parts of the watershed with access to irrigation and startup capital. Interventions promoting commercialization, such as those of CEDEPAS Norte, may result in reduced soil degradation and decreased conversion of pastures to cropland. On the other hand, the evaluation results for PRONAMACHCS indicate how difficult it is to improve the standard of life of the population by focusing exclusively on soil and water conservation techniques. Thus, this analysis indicates that a combination of activities may be necessary in order to improve productivity in the short term and promote adoption of sustainable soil and water conservation techniques in the medium and long term.